مراحل تطور الفن التشكيلي في الجزائر - بن علي, بختة (كلية الأدب العربي والفنون, 2024)
تناولنا في دراستنا مراحل تطور الحركة الفنية التشكيلية في الجزائر من خلال تقديم قراءاة تحليلية للوحة الفنان التشكلي محمد اسياخم فلوحة المرأة والطفل جسدت المشاعر والاحاسيس الذاتية الداخلية المعبرة عن الالم والمعاناة للام وطفلها الى صور تعبيرية تحمل دلالات رمزية فكرية في نفس الوقت ، يرتكز موضوع العمل الفني عند اسياخم على معالجة الحالة الفردية منبعها المرأة فهي تشكل الموضوع الاساسي في اعماله حيث يظهر الجانب النفسي جليا في لوحاته التي ترجمها عن الوانه واشكاله المجردة فهي تعبر عن المعانات النفسية والاجتماعية للفنان In our study, we discussed the stages of development of the fine art movement in Algeria by providing analytical readings of the paintings of artists. The painting of the Woman and the Child by MohamdAsyakhem embodied the inner subjective feelings and sensations that express the pain and suffering of the mother and her child into expressive images that carry intellectual symbolic connotations at the same time. The subject of Asyakhem’s artistic work is based on treating the individual situation, originating from women, as it constitutes the basic subject in his works, as the psychological aspect appears clearly in his paintings, which he translated from his colors and abstract shapes, as they express the psychological and social suffering of the artist
قراءات تحليلية للأعمال الفنان محمد إسياخم لوحت المرأة والطفل أنموذجا
Keywords: الفن،الفن التشكيلي،القراءات التحليلة; Art ; fine art; analytical readings